Extraction of the Volatile Oil of Stachys lavandulifolia and Study the Activity of Antibacterial and Antioxidant - Al-Hamdani, Firas Hashim Kamar; Al-Saadi, Mohammed Hmood (Nahrain University College of Engineering Journal, 2014)
The volatile oil of Stachys lavandulifolia was extracted from the aerial parts of the plant, with colorless and has aromatic odor. The yield were represented in the weight percentage of extracted oil was obtained (0.195% w/w) at best condition. Effects of experimental parameters such as temperature at (40 - 100) C? and the time (1 - 5) hrs on the efficiency of the extraction were studied.The experiments were designed by using Box-Wilson method, a relationship between the above two experimental parameters and weight percentage of extracted oil were obtained. The experimental data were fitted to second order polynomial methods, and the optimum conditions for the extraction process were obtained.The chemical composition of extracted volatile oil was analyzed by GC/MS showed the presence of fifty fife components representing (96.4)% of the volatile oil. The main components were ?-Thujene (3.8)%, ?-Pinene (7.8)%, ?-Pinene (8.2)%, Myrcene (11.4)%, ?-Phellandrene (14.9)%, Z-?-Ocimene (5.0)%, germacrene-D (16.1)%.The volatile oil has limited inhibition and show activity against gram positive comparative with gram negative. Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae were more resistance of volatile oil, which showed good antioxidant activity.